2019
DOI: 10.13075/ijomeh.1896.01436
|View full text |Cite
|
Sign up to set email alerts
|

Needs and possibilities for ship’s crews at high seas to communicate with their home

Abstract: Objectives: Good communication between seafarers and their families at home is essential to compensate for the work-related strain experienced on board ships. This paper presents the needs and possibilities for communication with home in seafaring. Material and Methods: In total, 323 seafarers were interviewed during their work assignments on board (the participation rate of 88.5%). The results were stratified by cultural background, family ties, rank groups and shipping routes. Results: The average stay of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…By contrast, the percentage of active workers was significantly higher among officers (30% vs. 5.1%) [13]. Oldenburg and Jensen [14] found that insufficient opportunities for telecommunication were experienced as a work-related strain among seafarers assigned to worldwide destinations (OR 1.87, 95% CI 1.15-3.04) and crew members without children (OR 2.00, 95% CI 1.03-3.88). Moreover, in another interview-based study with 337 seafarers employed on Chinese-flagged ships, An et al [15] found a significant, negative correlation between work performance and both work-family conflict (p < 0.05) and occupational stress (p < 0.05).…”
Section: Seafarers' Mental Health and Associated Factorsmentioning
confidence: 96%
“…By contrast, the percentage of active workers was significantly higher among officers (30% vs. 5.1%) [13]. Oldenburg and Jensen [14] found that insufficient opportunities for telecommunication were experienced as a work-related strain among seafarers assigned to worldwide destinations (OR 1.87, 95% CI 1.15-3.04) and crew members without children (OR 2.00, 95% CI 1.03-3.88). Moreover, in another interview-based study with 337 seafarers employed on Chinese-flagged ships, An et al [15] found a significant, negative correlation between work performance and both work-family conflict (p < 0.05) and occupational stress (p < 0.05).…”
Section: Seafarers' Mental Health and Associated Factorsmentioning
confidence: 96%
“…For example, in a 2003 study based on qualitative interviews with seafarers' partners in China, India and the UK, Thomas et al [42] concluded that separation from family was the main cause of stress for seafarers. In a recent study, Oldenburg and Jensen [27] found that "good" communication with people at home was critical to mitigate the stresses and pressures felt by seafarers while away from their families. In a digital context, Tang [39,40] explored the role of online support groups for seafarer partners, highlighting the tension between the empowering and disempowering effects of such groups [40] as well as how group members shared feelings and experiences of separation [39].…”
Section: Communicating At Seamentioning
confidence: 99%
“…Seafarers' missions also allow seafarers to satisfy their religious needs; this is particularly important for Filipino seafarers, who are quite religious and form the largest group worldwide. Furthermore, stressful experiences can be reduced through improved telephone contacts with the family at home [35,36].…”
Section: Engine Room Ratings (N = 8)mentioning
confidence: 99%